Construction and evaluation of efficient solid-state anaerobic digestion system via vinegar residue. (September 2018) - Zhou, Yunlong; Xu, Zhiyang; Zhao, Mingxing; Shi, Wansheng; Huang, Zhenxing; He, Di; Ruan, Wenquan
Abstract: Anaerobic digestion is a feasible method for vinegar residue disposal. However, its treatment efficiency is limited significantly by the low degradation of lignocellulose. In this study, a stable and efficient anaerobic digestion system for vinegar residue was constructed. The continuous solid-state reactor achieved a specific production of 418 mL·g-1 VS biogas and 223 mL·g-1 VS methane at a high organic loading rate (OLR) of 5.83 gVS ·(L·d) −1 . The stable degradation of lignocellulose between 39.5% and 36.4% was key factor for stable anaerobic digestion at high OLR. This stability under optimum OLR was due to the increase in the degradation of hemicellulose, which compensated for the loss of lignocellulose degradation. The enrichment of microorganism related to lignocellulose hydrolysis and the stable microbial community structure ensured efficient anaerobic digestion under high OLR condition. Digestion efficiency can be further improved mainly by increasing cellulose degradation. This investigation provided the theoretical basis for practical application of this digestion system for solid vinegar residue treatment. Graphical abstract: Highlights: A stable efficient anaerobic digestion system via vinegar residue was constructed. Optimum organic loading rate reached up to 5.83gVS ·(L·d) −1 . Increasing of hemicellulose hydrolysis rate stabilized system efficiency. Potential improvement on efficiency was depended on cellulose released and hydrolysis. Growth and uniform distribution of hydrolysis microbes ensured system efficiency.